2019
DOI: 10.3847/1538-4357/ab29fb
|View full text |Cite
|
Sign up to set email alerts
|

Hyper Wide Field Imaging of the Local Group Dwarf Irregular Galaxy IC 1613: An Extended Component of Metal-poor Stars

Abstract: Stellar halos offer fossil evidence for hierarchical structure formation. Since halo assembly is predicted to be scale-free, stellar halos around low-mass galaxies constrain properties such as star formation in the accreted subhalos and the formation of dwarf galaxies. However, few observational searches for stellar halos in dwarfs exist. Here we present gi photometry of resolved stars in isolated Local Group dwarf irregular galaxy IC 1613 (M ∼ 10 8 M ). These Subaru/Hyper Suprime-Cam observations are the wide… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 74 publications
1
20
0
Order By: Relevance
“…IC 1613 is another massive dwarf in Solo and has been well studied, including by Bernard et al (2007) and recently by Pucha et al (2019). Pucha et al (2019) found strong age gradients, and the young stellar population has a considerably smaller scale radius than the older stars. The SFH they determined is consistent with this picture, with a decreasing star formation rate with increasing radius.…”
Section: Ic 1613mentioning
confidence: 99%
See 3 more Smart Citations
“…IC 1613 is another massive dwarf in Solo and has been well studied, including by Bernard et al (2007) and recently by Pucha et al (2019). Pucha et al (2019) found strong age gradients, and the young stellar population has a considerably smaller scale radius than the older stars. The SFH they determined is consistent with this picture, with a decreasing star formation rate with increasing radius.…”
Section: Ic 1613mentioning
confidence: 99%
“…The allure of detecting halos around dwarfs lies in our desire to better understand their formation, whether they are a result of mergers or in-situ star formation. Pucha et al (2019) claim they identify a "halo" in IC 1613, finding the older, extended stellar component exhibits a different density profile to the more compact stellar component. However, the stellar densities in question are very low and they caution against over interpretation as a halo.…”
Section: Dwarfs Versus Larger Galaxiesmentioning
confidence: 99%
See 2 more Smart Citations
“…It has long been observed that dwarf galaxies host extended, round old stellar populations reminiscent in structure to the stellar halos of massive galaxies (Lin & Faber 1983;Minniti & Zijlstra 1996;Minniti et al 1999;Zaritsky et al 2000;Hidalgo et al 2003;Demers et al 2006;Bernard et al 2007;Stinson et al 2009;Strader et al 2012;Nidever et al 2019a,b;Pucha et al 2019;Kado-Fong et al 2020). Recently, it has been shown that high-mass dwarfs (10 8.5 < M < 10 9.6 M ) can form a thick stellar & HI disk (Roychowdhury et al 2013;van der Wel et al 2014;Nath Patra 2020) in conjunction with a round stellar halo (Kado-Fong et al 2020).…”
Section: Introductionmentioning
confidence: 99%